Teaching english literature in costa rican experimental bilingual high schools: EFL teachers' academic training. - Karla Araya Araya; Priscila Campos Rosales; Erika González Mora; Gerardina Marín Madrigal; Kattia Rojas Suárez; Catalina Sánchez Alvarado (Universidad Autónoma de Baja California, 2017)
This article presents the most relevant results found in the "Licenciatura" graduation research project for the BA in Teaching English offered by the University of Costa Rica, Campus Occidente. The work, entitled "Strengths and Weaknesses in Teaching English Literature in Experimental Bilingual High Schools of the Western Educational Region of Costa Rica: A Study from the Teachers' Perspectives", was conducted in 2012 and 2013. 36 EFL teachers participated. This paper presents results on the strengths and weaknesses of teachers' academic and professional training in light of the implementation of the English literature syllabus of the Costa Rican Ministry of Public Education (known by the acronym MEP in Spanish). Qualitative and quantitative methodologies were used. Interviews were conducted with participants and English advisors and an online survey was also used. Results show that most EFL teachers do not feel trained to deal with the English literature syllabus because teaching literature is not their major, but the MEP has assumed that mastering the language is sufficient for an English teacher to teach literature. Most teachers reject this presupposition as they think that the MEP'S English literature syllabus focuses on literary content rather than using literature to teach and learn English. Teachers assert that there is a discrepancy between their academic training and what the MEP expects them to do.